China's National Education Conference Matters: Major Education Discursive Blueprinting in 2024 - Yansi Hou (侯滟斯) (ECNU Review of Education)
Purpose This study aims to analyze the blueprint for China's future education development outlined in China's National Education Conference of September 2024 and to examine the role of conference speeches in shaping China's education policymaking. Design/Approach/Methods This study thematically analyzed both the conference speech and the related press releases. Findings Regarding the speech content, five key tasks outlined in the conference speeches for building a strong education system by 2035 were identified. These tasks address the public's demand for high-quality education and the needs of national development. Regarding the speech structure, the conference speeches were structured into four main parts, each serving a distinct function in shaping education policy. Originality/Value This study contributes to a deeper understanding of China's recent policy directions for education development. It also sheds light on the discursive blueprinting function of conference speeches in China's education policymaking process.